The Formulation Policy of the Death Penalty in the New Criminal Code and Its Problems regarding the Principle of the Right to Life as a Non Derogable Right - Sonya Evalin Br. Silalahi; Sumarno Sumarno; Suci Ramadani; Andronius Basado Siahaan; Martinus Bosko Sinaga (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The dynamics of the death penalty in Indonesia have undergone significant changes in tandem with the revision of the Criminal Code (KUHP). The death penalty is the oldest form of punishment, involving the taking of the life of a perpetrator of a serious crime, and has been part of the Indonesian legal system from the era of kingdoms to the modern era. The implementation of the death penalty in Indonesia has evolved, ranging from traditional methods to executions by firing squad in accordance with statutory regulations. The reform of criminal law in Indonesia has become an increasingly urgent necessity in light of social developments, technological advancements, and the increasingly complex and diverse nature of crime. Law No. 1 of 2023 on the new Criminal Code (KUHP) serves as a comprehensive effort to replace the colonial-era Criminal Code and align the national criminal justice system with the current conditions of Indonesian society. This study aims to examine the current policy on the formulation of the death penalty in Indonesia’s criminal legislation and to analyze the envisioned legal framework regarding the death penalty in Indonesia for the future. The application of this punishment has sparked a heated debate between those who support it viewing the death penalty as a deterrent and an exceptional tool for crime prevention—and those who oppose it on the grounds of human rights violations and the risk of injustice. The methodology used in this study is juridical-normative, utilizing secondary data from legal regulations, literature, and academic journals. The approach applied is a conceptual one, analyzing the discussion from the perspective of relevant theories and concepts. The analysis is conducted qualitatively by examining the application of the death penalty model from the perspective of criminal law theory. This approach reflects an orientation toward rehabilitation and respect for human rights.